Effects of Provision of Concrete Information about Patient-controlled Analgesia in Hysterectomy Patients - Bo Gyeong Lee; Young Whee Lee (Korean Society of Women Health Nursing, 2014)
PURPOSE: This study was to investigate the effects of the provision of concrete information about patient-controlled analgesia (PCA) in hysterectomy patients. METHODS: Study design was a nonequivalent control group non-synchronized pre- and post-test design. Sixty subjects participated were assigned to experimental group (30 patients) or control group (30 patients) at one university hospital. Concrete information about PCA was composed of three sections: explanation with a leaflet, practice of using PCA, and question and answer session. RESULTS: The experimental group who received concrete information about PCA before surgery had statistically higher knowledge level about PCA, more positive attitude toward pain control analgesia, a lower pain score, and a higher satisfaction level of the use of PCA post-surgery compared to the control group who received general information before surgery. CONCLUSION: Provision of concrete information about PCA was an effective nursing intervention that reduced post-operative pain for patients and increased their satisfaction with using PCA. It is recommended that concrete information about PCA be provided by nurses to promote the use of PCA and consequently reduce patient's pain post-surgery.